Lack of PTEN in osteocytes increases circulating phosphate concentrations by decreasing intact fibroblast growth factor 23 levels - Masanobu Kawai (Nature Portfolio, 2020)
Abstract Fibroblast growth factor 23 (FGF23) has been centric to the regulation of phosphate (Pi) metabolism; however, the regulatory network of FGF23 in osteocytes has not yet been defined in detail. We herein investigated the role of PTEN (phosphatase and tensin homolog deleted from chromosome 10) in this regulation. We created mice lacking PTEN expression mainly in osteocytes by crossing Pten-flox mice with Dmp1-Cre mice. The lack of PTEN in the osteocytes of these mice was associated with decreased skeletal and serum intact FGF23 levels, which, in turn, resulted in reductions of urinary Pi excretion and elevations of serum Pi levels. Mechanistically, the knockdown of PTEN expression in osteoblastic UMR106 cells activated the AKT/mTORC1 (mechanistic target of rapamycin complex 1) pathway and this was associated with reductions in Fgf23 expression. Furthermore, the suppression of Fgf23 expression by PTEN knockdown or insulin simulation in UMR106 cells was partially restored by the treatment with the mTORC1 inhibitor, rapamycin. These results suggest that FGF23 expression in osteoblastic cells is in part regulated through the AKT/mTORC1 pathway and provide new insights into our understanding of the regulatory network of Pi metabolism.